Sensitivity of the circadian system to evening bright light in preschool‐age children. Issue 5 (4th March 2018) - Akacem, Lameese D.; Wright, Kenneth P.; LeBourgeois, Monique K.
Abstract: Although the light‐induced melatonin suppression response is well characterized in adults, studies examining the dynamics of this effect in children are scarce. The purpose of this study was to quantify the magnitude of evening light‐induced melatonin suppression in preschool‐age children. Healthy children ( n  = 10; 7 females; 4.3 ± 1.1 years) participated in a 7‐day protocol. On days 1–5, children followed a strict sleep schedule. On day 6, children entered a dim light environment (<15 lux) for 1‐h before providing salivary samples every 20‐ to 30‐min from the afternoon until 50‐min after scheduled bedtime. On day 7, subjects remained in dim light conditions until 1‐h before bedtime, at which time they were exposed to a bright light stimulus (~1000 lux) for 1‐h and then re‐entered dim light conditions. Saliva samples were obtained before, during, and after bright light exposure and were time anchored to samples taken the previous evening. We found robust melatonin suppression (87.6 ± 10.0%) in response to the bright light stimulus. Melatonin levels remained attenuated for 50‐min after termination of the light stimulus ( P  < 0.008). Furthermore, melatonin levels did not return to 50% of those observed in the dim light condition 50‐min after the light exposure for 7/10 children. Our findings demonstrate a robust light‐induced melatonin suppression response in preschool‐age children. These findings have implications for understanding the role of evening light exposure in the development of evening settling difficulties and may serve as experimental evidence to support recommendations regarding light exposure and sleep hygiene practices in early childhood. Abstract : In this study, we examined melatonin suppression in response to 1‐h of bright light exposure before bedtime and found that this exposure suppressed children's melatonin secretion by ~88%. Furthermore, melatonin levels remained attenuated for 50‐min after termination of the evening bright light stimulus. We believe our findings have important implications for understanding fundamental circadian physiology in young children and the role of light in childhood sleep disturbances